Women's empowerment for farm resilience in Ethiopia: A three-step approach for latent class analysis - Bekhzod Egamberdiev; Mukhayo Djuraeva; Abdulla Primov (Review of Agricultural, Food and Environmental Studies, 2026)
Farm resilience to withstand shocks and stresses has become a key topic in research and policy debates. However, disproportionate behavior toward women's empowerment may underestimate farm resilience capacity. We examine the effects of gender equality on farm resilience capacity, with a focus on land ownership and decision-making processes. By using the Living Standard Measurement Survey–Plus by the World Bank, we construct the farm's robust capacity (RC), adaptive capacity (AC), and transition capacity (TC) in the first stage and farm resilience capacity (FRC) in the second stage of factor analysis. We also apply a latent class approach to identify homogenous households representing “low gender equality” and “high gender equality” topologies. We apply a three-step approach to identify the relationship between latent classes and resilience. The findings reveal a positive and significant relationship between the “high gender equality” class and AC or FRC compared to those households representing “low gender equality.” In conclusion, it is imperative to strengthen women's empowerment through ownership and decision-making to enhance farm resilience capacity. A key contribution of this study was to understand the importance of access to resources and the decision-making of women to improve farm resilience in Ethiopia.
Keywords: J16; Q10; Q12; N57; 630; farm resilience; capacity; gender equality; Ethiopia